### Home > CAAC > Chapter 10 > Lesson 10.4.3 > Problem 10-149

10-149.

You can use the substitution method.

10*y* − (8*y* − 1) = 5

Solve for y.

10 − 8*y* + 1 = 5

2*y* = 4*y* = 2

Substitute *y* into one of the equations and solve for *x*.

8(2) − 1 = *x*

16 − 1 = *x**x* = 15

(15, 2)

You can use the substitution method.

−4*x* − 2 = *x*^{2} − 3*x* − 4

Set the equation equal to zero.

0 = *x*^{2} − 3*x* + 4*x* − 4 + 2*x*^{2} + *x* − 2 = 0

Solve for *x*.

Factor:

(*x* − 1)(*x* + 2) = 0*x* − 1 = 0 x + 2 = 0*x* = 1 *x* = −2

Substitute both *x*'s into one of the equations to solve for *y*.

*y* = −4(1) − 2 *y* = −4(−2) − 2 *y* = −6 *y* = 6

(1, −6) (−2, 6)